1. Start with 5 and subtract –9 repeatedly. The rule is: nth term = 5 - (n-1)9
2. -2 x (-6) = 12, 12 x (-6) = -72, -72 x (-6) = 432. So the next three terms are -2 x (-6 x (-6)) = 864, 864 x (-6) = -5,184, -5,184 x (-6) = 31,104.
3. To find the 9th term, we need to add 6 to each term to get: 17, 23, 29, 35, 41, 47, 53, 59, 65. The 9th term is 59.
1. Write a rule for the sequence. (1 point) 5, –4, –13, –22,...
Start with –9 and add 5 repeatedly. Start with 5 and add 9 repeatedly.
Start with 5 and subtract –9 repeatedly. Start with 5 and add –9 repeatedly.
2. Find the next three terms of the sequence. –2, –12, –72, –432, ...
–1,728, –6,912, –27,648 –1,728, –10,368, –62,208 –2,592, –10,368, –41,472 –2,592, –15,552, –93,312
3. What is the 9th term in the following sequence?
11, 17, 23, 29, . . .
47 53 59 65
1 answer